StarPure endotoxin-free ultrapure plasmid large extraction kit

By using modified copolymerized magnetic beads and magnetic nanoseparation technology in plasmid DNA extraction, the existing plasmid DNA extraction methods are solved, and the rapid and efficient extraction of plasmid DNA is achieved.

CN119391695APending Publication Date: 2025-02-07KANGRUNJINGXING (SUZHOU) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411563657.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing plasmid DNA extraction method is cumbersome and takes a long time, and there is a problem of insufficient adsorption of magnetic beads on DNA, resulting in a long extraction time.

Method used

The StarPure endotoxin-free ultrapure plasmid extraction kit is used to improve the extraction efficiency and speed through the specific adsorption of modified copolymerized magnetic beads after surface modification and combined with magnetic nanoseparation technology.

Benefits of technology

The rapid and efficient extraction of plasmid DNA is achieved, reducing operational complexity and time-consuming, and improving extraction efficiency and purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118600370000101
    Figure BDA0005118600370000101
Patent Text Reader

Abstract

The invention discloses a StarPure endotoxin-free ultrapure plasmid extraction kit, and relates to the technical field of milling cutter composite coatings. According to the invention, specific adsorption between the surface-modified magnetic beads and plasmids is adopted, and a magnetic nano separation technology is adopted, so that the method has the advantages of convenience and good repeatability; the magnetic bead adopts methyl acrylate and vinyl pyridine copolymer as a main body, the surface of the main body is covered with Fe3O4 (at) SiO2 magnetic nanoparticles, and the surfaces of the Fe3O4 (at) SiO2 magnetic nanoparticles are grafted with allyltrimethoxysilane, so that the dispersity of the Fe3O4 (at) SiO2 magnetic nanoparticles in a solution can be improved, and the Fe3O4 (at) SiO2 magnetic nanoparticles are uniformly dispersed on the surface of the copolymer; on the other hand, the copolymerized magnetic beads are firmly fixed on the surface of a copolymer through double bonds on allyltrimethoxysilane, and finally, the surfaces of the copolymerized magnetic beads are covered with a layer of SiO2 again through sol-gel reaction of tetraethoxysilane in an ammonia water medium, so that the surfaces of the copolymerized magnetic beads have a large number of silicon hydroxyl groups, and specific adsorption is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plasmid extraction kits, in particular to a StarPure endotoxin-free ultrapure plasmid extraction kit. Background Art

[0002] In the prior art, the extraction method of bacterial plasmid DNA generally includes the steps of bacterial lysis, DNA aggregation and precipitation, impurity removal, DNA purification and separation, etc. Traditional extraction methods mainly include column method and CTAB lysis method, which are cumbersome and time-consuming, not conducive to large-scale extraction, and organic solvents such as chloroform and phenol may be used during the operation, which are highly polluting.

[0003] The magnetic bead bacterial plasmid DNA extraction kit utilizes the specific adsorption of surface-modified magnetic beads and DNA molecules and adopts magnetic nano-separation technology, which has the advantages of convenience and good repeatability. However, the magnetic bead bacterial plasmid DNA extraction method reported today has the problem of insufficient adsorption of DNA by magnetic beads, resulting in a long extraction time. Therefore, it is necessary to develop a high-throughput bacterial plasmid DNA extraction method with fast extraction speed and high extraction efficiency. Summary of the invention

[0004] The object of the present invention is to provide a StarPure endotoxin-free ultrapure plasmid extraction kit to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The StarPure endotoxin-free ultrapure plasmid extraction kit includes a suspension, a lysis solution, a binding solution, a washing solution and an elution solution, and also includes a modified copolymer magnetic bead suspension, wherein the modified copolymer magnetic bead suspension is prepared by mixing the modified copolymer magnetic beads and isopropanol in a mass ratio of 1:10 to 20;

[0007] The modified copolymer magnetic beads include the following preparation steps:

[0008] S1. Add Fe3O4@SiO2 magnetic nanoparticles to anhydrous toluene with a mass of 4 to 5 times that of Fe3O4@SiO2 magnetic nanoparticles, ultrasonically disperse for 10 to 15 minutes, then add allyltrimethoxysilane with a mass of 3 to 4 times that of Fe3O4@SiO2 magnetic nanoparticles, stir and react for 24 to 26 hours at a temperature of 105 to 115°C and a speed of 300 r / min, transfer to a centrifuge tube after the reaction is completed, and centrifuge for 10 to 12 minutes at a temperature of 25 to 35°C and a speed of 8000 r / min to obtain modified Fe3O4@SiO2 magnetic nanoparticles;

[0009] S2, adding sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinylpyridine to deionized water 3 to 5 times the mass of methyl methacrylate, then adding modified Fe3O4@SiO2 magnetic nanoparticles 0.08 to 0.1 times the mass of methyl methacrylate, stirring evenly, stirring and reacting for 30 to 40 minutes at a temperature of 35 to 40 ° C, then adding N, N'-tetramethylethylenediamine 0.8 to 1.2 times the mass of methyl methacrylate, stirring evenly, reacting for 3 to 3.5 hours, standing for 1 to 2 hours after the reaction, and then washing the product with acetone and deionized water for 3 to 4 times respectively to prepare copolymer magnetic beads;

[0010] S3. Add the copolymer magnetic beads to an ammonia solution with a mass fraction of 25-28% which is 10-15 times the mass of the copolymer magnetic beads to swell; at a temperature of 0-5°C and under nitrogen protection, add n-heptane with a mass fraction of 600-700 times the mass of the copolymer magnetic beads, stir for 30-40 minutes at a rotation speed of 450-500r / min, and then add 5-6 times the mass of the copolymer magnetic beads of tetraethyl orthosilicate solution at a uniform speed of 1mL / S. After the addition is completed, continue to stir the reaction for 3-4h. After the reaction is completed, filter, and use acetone and deionized water to wash the filtered product for 3-4 times respectively, and then dry it naturally to obtain modified copolymer magnetic beads.

[0011] As an optimization, the Fe3O4@SiO2 magnetic nanoparticles include the following preparation steps: adding Fe3O4 magnetic nanoparticles to deionized water with a mass of 180 to 200 times that of the Fe3O4 magnetic nanoparticles, stirring for 10 to 20 minutes under nitrogen protection conditions, heating to 75 to 85°C after uniform stirring, then dripping a Na2SiO3 solution with a mass of 20 to 22 times that of the Fe3O4 magnetic nanoparticles at a rate of 10 mL / h, and adjusting the pH to 6 to 6.5 with a hydrochloric acid solution with a mass fraction of 36 to 38%, stirring the reaction for 3 to 3.5 hours after the dripping is completed, performing magnetic separation after the stirring is completed, and washing the separated product with anhydrous ethanol and deionized water for 3 to 5 times respectively, and then vacuum drying at a temperature of 55 to 65°C for 14 to 16 hours to obtain Fe3O4@SiO2 magnetic nanoparticles.

[0012] As an optimization, the mass fraction of the Na2SiO3 solution is 12-14%.

[0013] As an optimization, the Fe3O4 magnetic nanoparticles include the following preparation steps: adding FeCl3·6H2O to ethylene glycol with a mass of 30 to 35 times that of FeCl3·6H2O, stirring for 30 to 35 minutes, then adding anhydrous sodium acetate and polyethylene glycol, and continuing to stir for 30 to 35 minutes. After stirring, reacting at a temperature of 200 to 210°C for 48 to 50 hours, and after the reaction is completed, performing magnetic separation, and washing the separated products with anhydrous ethanol and deionized water for 3 to 5 times respectively, and then vacuum drying at a temperature of 55 to 65°C for 24 to 26 hours to obtain Fe3O4 magnetic nanoparticles.

[0014] As an optimization, the mass of the anhydrous sodium acetate is 2.5 to 2.8 times that of FeCl3·6H2O.

[0015] As an optimization, the polyethylene glycol is 0.7 to 0.75 times the mass of FeCl3·6H2O.

[0016] As an optimization, the ethyl orthosilicate solution is prepared by mixing ethyl orthosilicate and n-heptane in a volume ratio of 1:4.

[0017] As an optimization, the mass ratio of the sodium hydroxide, N,N′-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.28-0.3: 0.22-0.24: 0.8-0.9: 1: 0.8-0.9.

[0018] The extraction method of the StarPure Endotoxin-Free Ultrapure Plasmid Extraction Kit is to extract using the StarPure Endotoxin-Free Ultrapure Plasmid Extraction Kit described above, and comprises the following steps:

[0019] Step (1), transferring the bacterial culture solution into a sterilized centrifuge tube, and collecting the bacterial precipitate by centrifugation;

[0020] Step (2), adding the suspension to the bacterial precipitate of step (1), vortexing and oscillating to obtain a bacterial suspension;

[0021] Step (3), adding a lysis solution to the bacterial suspension of step (2) to lyse the bacterial precipitate to obtain a bacterial lysate;

[0022] Step (4), adding the binding solution to the bacterial lysate of step (3), centrifuging, taking the supernatant and transferring it to a centrifuge tube, then adding the modified copolymer magnetic bead suspension, standing at 25 to 35° C. for 3 to 5 minutes, and then placing the centrifuge tube in the magnetic field of a magnetic stand to remove the residual liquid;

[0023] Step (5), adding washing solution to the centrifuge tube from which the residual liquid is removed in step (4), shaking and inverting 2 to 3 times, placing the tube in the magnetic field of the magnetic stand again, removing the residual liquid, repeating the process once, keeping the tube at rest for 5 to 10 minutes at 25 to 35° C., adding eluent, incubating at 25 to 35° C. for 3 to 5 minutes, placing the tube in the magnetic field again, extracting the remaining solution, and storing it at -20° C. The resulting solution is the high-purity plasmid obtained by extraction.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] The specific adsorption between the surface-modified magnetic beads and the plasmids used in the present application adopts magnetic nano-separation technology, which has the advantages of convenience and good repeatability; the magnetic beads use methyl acrylate and vinyl pyridine copolymer as the main body, and Fe3O4@SiO2 magnetic nanoparticles are covered on the surface thereof, and allyl trimethoxysilane is grafted on the surface of the Fe3O4@SiO2 magnetic nanoparticles to improve their dispersibility in the solution, so that they are evenly dispersed on the surface of the copolymer, and on the other hand, the double bonds on the allyl trimethoxysilane firmly fix them on the surface of the copolymer, and finally a layer of SiO2 is covered on the surface of the copolymer magnetic beads again through the sol-gel reaction of tetraethoxysilane in an ammonia medium, so that the surface thereof has a large number of silanol groups, thereby achieving specific adsorption;

[0026] In the copolymerization process, methyl acrylate and vinyl pyridine are used for copolymerization to prepare the copolymer magnetic bead body, which can swell under alkaline conditions and shrink under acidic conditions. Since the alkaline lysis method commonly used in the plasmid preparation process will cause the final extraction solution to be alkaline, methyl acrylate and vinyl pyridine are used to make it swell under alkaline conditions, thereby increasing the contact surface area of ​​the magnetic beads, so that more plasmids are attached to them, and they shrink in the elution solution to accelerate the separation of the plasmid;

[0027] After the preparation of the copolymer magnetic beads is completed, a layer of SiO2 is deposited on its surface in order to make it contain more silanol groups and convert part of the surface siloxane into silanol groups. In order to avoid the deposition of too much SiO2 and weaken its swelling ability, the deposition time is controlled to half of that of the traditional preparation, thereby ensuring that the final modified copolymer magnetic beads have good swelling ability. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] S1. Add FeCl3·6H2O to ethylene glycol with a mass of 30 times that of FeCl3·6H2O, stir for 30 minutes, then add anhydrous sodium acetate and polyethylene glycol, continue stirring for 30 minutes, react at 200°C for 48 hours, separate by magnetic force after the reaction is completed, and wash the separated product with anhydrous ethanol and deionized water for 3 times respectively, and then vacuum dry at 55°C for 24 hours to obtain Fe3O4 magnetic nanoparticles; the mass of anhydrous sodium acetate is 2.5 times that of FeCl3·6H2O; the mass of polyethylene glycol is 0.7 times that of FeCl3·6H2O;

[0031] S2. Add Fe3O4 magnetic nanoparticles to deionized water with a mass of 180 times that of Fe3O4 magnetic nanoparticles, stir for 10 minutes under nitrogen protection, and after stirring evenly, heat to 75°C, then drip Na2SiO3 solution with a mass of 22 times that of Fe3O4 magnetic nanoparticles at a rate of 10mL / h, and adjust the pH to 6 with a hydrochloric acid solution with a mass fraction of 36%. After the dripping is completed, stir and react for 3 hours. After the stirring is completed, separate by magnetic force, and wash the separated product with anhydrous ethanol and deionized water for 3 times respectively, and then vacuum dry at a temperature of 55°C for 14 hours to obtain Fe3O4@SiO2 magnetic nanoparticles; the mass fraction of Na2SiO3 solution is 12%;

[0032] S3, adding Fe3O4@SiO2 magnetic nanoparticles to anhydrous toluene with a mass of 4 times that of Fe3O4@SiO2 magnetic nanoparticles, ultrasonically dispersing for 10 minutes, then adding allyltrimethoxysilane with a mass of 3 times that of Fe3O4@SiO2 magnetic nanoparticles, stirring and reacting for 24 hours at a temperature of 105°C and a speed of 300r / min, transferring to a centrifuge tube after the reaction, centrifuging for 10 minutes at a temperature of 25°C and a speed of 8000r / min, to obtain modified Fe3O4@SiO2 magnetic nanoparticles;

[0033] S4, adding sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine to deionized water 3 times the mass of methyl methacrylate, then adding modified Fe3O4@SiO2 magnetic nanoparticles 0.08 times the mass of methyl methacrylate, stirring evenly, stirring and reacting for 30 minutes at a temperature of 35°C, then adding N, N'-tetramethylethylenediamine 0.8 times the mass of methyl methacrylate, stirring evenly, reacting for 3 hours, standing for 1 hour after the reaction, and then washing the product with acetone and deionized water for 3 times respectively to prepare copolymer magnetic beads; the mass ratio of sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.28:0.22:0.8:1:0.8;

[0034] S5. Add the copolymer magnetic beads to a 25% ammonia solution with a mass fraction of 10 times the mass of the copolymer magnetic beads to swell; at a temperature of 0°C and under nitrogen protection, add n-heptane with a mass fraction of 600 times the mass of the copolymer magnetic beads, stir at a speed of 450r / min for 30 minutes, and then add 5 times the mass of the copolymer magnetic beads The tetraethyl orthosilicate solution is uniformly added at a speed of 1mL / S. After the addition is completed, continue to stir and react for 3 hours. After the reaction is completed, filter and use acetone and deionized water to wash the filtered product for 3 times respectively, and then dry it naturally to obtain modified copolymer magnetic beads; the tetraethyl orthosilicate solution is prepared by mixing tetraethyl orthosilicate and n-heptane in a volume ratio of 1:4.

[0035] Example 2

[0036] S1. Add FeCl3·6H2O to ethylene glycol with a mass of 32 times that of FeCl3·6H2O, stir for 32 minutes, then add anhydrous sodium acetate and polyethylene glycol, continue stirring for 32 minutes, react at 205°C for 49 hours, separate by magnetic force after the reaction is completed, and wash the separated product with anhydrous ethanol and deionized water for 5 times respectively, and then vacuum dry at 60°C for 24 hours to obtain Fe3O4 magnetic nanoparticles; the mass of anhydrous sodium acetate is 2.7 times that of FeCl3·6H2O; the mass of polyethylene glycol is 0.73 times that of FeCl3·6H2O;

[0037] S2. Add Fe3O4 magnetic nanoparticles to deionized water with a mass of 190 times that of Fe3O4 magnetic nanoparticles, stir for 15 minutes under nitrogen protection, and after stirring evenly, heat to 80°C, then drip Na2SiO3 solution with a mass of 21 times that of Fe3O4 magnetic nanoparticles at a rate of 10 mL / h, and adjust the pH to 6 with a hydrochloric acid solution with a mass fraction of 36%. After the dripping is completed, stir and react for 3 hours. After stirring, separate by magnetic force, and wash the separated product with anhydrous ethanol and deionized water for 5 times respectively, and then vacuum dry at 60°C for 15 hours to obtain Fe3O4@SiO2 magnetic nanoparticles; the mass fraction of Na2SiO3 solution is 14%;

[0038] S3, adding Fe3O4@SiO2 magnetic nanoparticles to anhydrous toluene with a mass of 4.5 times that of Fe3O4@SiO2 magnetic nanoparticles, ultrasonically dispersing for 12 minutes, then adding allyltrimethoxysilane with a mass of 4 times that of Fe3O4@SiO2 magnetic nanoparticles, stirring and reacting for 25 hours at a temperature of 110°C and a speed of 300r / min, transferring to a centrifuge tube after the reaction, centrifuging for 12 minutes at a temperature of 30°C and a speed of 8000r / min, to obtain modified Fe3O4@SiO2 magnetic nanoparticles;

[0039] S4, adding sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine to deionized water 4 times the mass of methyl methacrylate, then adding modified Fe3O4@SiO2 magnetic nanoparticles 0.09 times the mass of methyl methacrylate, stirring evenly, stirring and reacting for 35 minutes at a temperature of 40°C, then adding N, N'-tetramethylethylenediamine 1 times the mass of methyl methacrylate, stirring evenly, reacting for 3.5 hours, standing for 1.5 hours after the reaction, and then washing the product with acetone and deionized water for 4 times respectively to prepare copolymer magnetic beads; the mass ratio of sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.29:0.23:0.85:1:0.85;

[0040] S5. Add the copolymer magnetic beads to a 27% ammonia solution with a mass fraction of 12 times the mass of the copolymer magnetic beads to swell; at a temperature of 0°C and under nitrogen protection, add n-heptane with a mass fraction of 650 times the mass of the copolymer magnetic beads, stir for 35 minutes at a rotation speed of 450r / min, and then add 5 times the mass of the copolymer magnetic beads The tetraethyl orthosilicate solution is uniformly added at a speed of 1mL / S. After the addition is completed, continue to stir and react for 3 hours. After the reaction is completed, filter and use acetone and deionized water to wash 4 times respectively, and then dry naturally to obtain modified copolymer magnetic beads; the tetraethyl orthosilicate solution is prepared by mixing tetraethyl orthosilicate and n-heptane in a volume ratio of 1:4.

[0041] Example 3

[0042] S1. Add FeCl3·6H2O to ethylene glycol with a mass of 35 times that of FeCl3·6H2O, stir for 35 minutes, then add anhydrous sodium acetate and polyethylene glycol, continue stirring for 35 minutes, react at 210°C for 50 hours, separate by magnetic force after the reaction is completed, and wash the separated product with anhydrous ethanol and deionized water for 5 times respectively, and then vacuum dry at 65°C for 26 hours to obtain Fe3O4 magnetic nanoparticles; the mass of anhydrous sodium acetate is 2.8 times that of FeCl3·6H2O; the mass of polyethylene glycol is 0.75 times that of FeCl3·6H2O;

[0043] S2. Add Fe3O4 magnetic nanoparticles to deionized water with a mass of 200 times that of Fe3O4 magnetic nanoparticles, stir for 20 minutes under nitrogen protection, and after stirring evenly, heat to 85°C, then drip Na2SiO3 solution with a mass of 22 times that of Fe3O4 magnetic nanoparticles at a rate of 10mL / h, and adjust the pH to 6.5 with a hydrochloric acid solution with a mass fraction of 38%. After the dripping is completed, stir and react for 3.5 hours. After stirring, separate by magnetic force, and wash the separated product with anhydrous ethanol and deionized water for 5 times respectively, and then vacuum dry at a temperature of 65°C for 16 hours to obtain Fe3O4@SiO2 magnetic nanoparticles; the mass fraction of Na2SiO3 solution is 14%;

[0044] S3, adding Fe3O4@SiO2 magnetic nanoparticles to anhydrous toluene with a mass of 5 times that of Fe3O4@SiO2 magnetic nanoparticles, ultrasonically dispersing for 15 minutes, then adding allyltrimethoxysilane with a mass of 4 times that of Fe3O4@SiO2 magnetic nanoparticles, stirring and reacting for 26 hours at a temperature of 115°C and a rotation speed of 300r / min, transferring to a centrifuge tube after the reaction, centrifuging for 12 minutes at a temperature of 35°C and a rotation speed of 8000r / min, to obtain modified Fe3O4@SiO2 magnetic nanoparticles;

[0045] S4, adding sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine to deionized water 5 times the mass of methyl methacrylate, then adding modified Fe3O4@SiO2 magnetic nanoparticles 0.1 times the mass of methyl methacrylate, stirring evenly, stirring and reacting for 40 minutes at a temperature of 40°C, then adding N, N'-tetramethylethylenediamine 1.2 times the mass of methyl methacrylate, stirring evenly, reacting for 3.5 hours, standing for 2 hours after the reaction, and then washing the product with acetone and deionized water for 4 times respectively to prepare copolymer magnetic beads; the mass ratio of sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.3:0.24:0.9:1:0.9;

[0046] S5. Add the copolymer magnetic beads to a 28% ammonia solution with a mass fraction of 15 times the mass of the copolymer magnetic beads to swell; at a temperature of 5°C and under nitrogen protection, add n-heptane with a mass fraction of 700 times the mass of the copolymer magnetic beads, stir for 40 minutes at a speed of 500r / min, and then add 6 times the mass of the copolymer magnetic beads The tetraethyl orthosilicate solution is uniformly added at a speed of 1mL / S. After the addition is completed, continue to stir and react for 4 hours. After the reaction is completed, filter and use acetone and deionized water to wash the filtered product for 4 times respectively, and then dry it naturally to obtain modified copolymer magnetic beads; the tetraethyl orthosilicate solution is prepared by mixing tetraethyl orthosilicate and n-heptane in a volume ratio of 1:4.

[0047] Example 4

[0048] The difference from Example 2 is only in step S4: sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine are added to deionized water with a mass of 5 times that of methyl methacrylate, and then Fe3O4@SiO2 magnetic nanoparticles with a mass of 0.1 times that of methyl methacrylate are added, stirred evenly, and reacted at a temperature of 40°C for 40 minutes, and then N, N'-tetramethylethylenediamine with a mass of 1.2 times that of methyl methacrylate is added, stirred evenly, and reacted for 3.5 hours. After the reaction is completed, the mixture is allowed to stand for 2 hours, and the product is washed 4 times with acetone and deionized water respectively to prepare copolymer magnetic beads; the mass ratio of sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.3:0.24:0.9:1:0.9;

[0049] Example 5

[0050] The difference from Example 2 is only in step S4: sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine are added to deionized water with a mass of 5 times that of methyl methacrylate, and then Fe3O4 magnetic nanoparticles with a mass of 0.1 times that of methyl methacrylate are added, stirred evenly, and reacted at a temperature of 40°C for 40 minutes, and then N, N'-tetramethylethylenediamine with a mass of 1.2 times that of methyl methacrylate is added, stirred evenly, and reacted for 3.5 hours. After the reaction is completed, the product is allowed to stand for 2 hours, and then the product is washed 4 times with acetone and deionized water respectively to prepare copolymer magnetic beads; the mass ratio of sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.3:0.24:0.9:1:0.9;

[0051] Example 6

[0052] The difference from Example 2 is only in step S4: sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate and methyl methacrylate are added to deionized water with a mass of 5 times that of methyl methacrylate, and then Fe3O4 magnetic nanoparticles with a mass of 0.1 times that of methyl methacrylate are added, stirred evenly, and reacted at a temperature of 40°C for 40 minutes, and then N, N'-tetramethylethylenediamine with a mass of 1.2 times that of methyl methacrylate is added, stirred evenly, and reacted for 3.5 hours. After the reaction is completed, the product is allowed to stand for 2 hours, and then the product is washed 4 times with acetone and deionized water respectively to prepare copolymer magnetic beads; the mass ratio of sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate and methyl methacrylate is 0.3:0.24:0.9:1;

[0053] Example 7

[0054] The only difference from Embodiment 2 is that step S5 is not performed;

[0055] Comparative Example 1

[0056] The final products prepared in the above Examples 1 to 7 were used as magnetic beads for standby use, and a group of commercially purchased magnetic beads were added as a control group; 20% PEG and 4 mol / L NaCl solution were used as DNA binding solution, and the plasmid extraction results were as shown in Table 1 below;

[0057] Table 1 Plasmid extraction results experimental data

[0058]

[0059] From the comparison of the experimental data in Table 1, it can be found that Examples 1 to 3 all maintain good extraction efficiency and are higher than commercially available magnetic beads. It can be expected that it will decline in Examples 4 to 5. The main reason for the decline may be due to the uneven distribution of magnetic particles. The main reason for the decline in Example 6 may be that the lack of vinylpyridine leads to a decrease in the swelling ability of the final magnetic beads. In the final Example 7, the final extraction efficiency is greatly reduced due to the lack of silanol in the outer layer.

[0060] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. StarPure endotoxin-free ultrapure plasmid extraction kit, including suspension, lysis solution, binding solution, washing solution and elution solution, characterized in that: Also included is a modified copolymer magnetic bead suspension, wherein the modified copolymer magnetic bead suspension is prepared by mixing the modified copolymer magnetic beads and isopropanol in a mass ratio of 1:10 to 20; The modified copolymer magnetic beads include the following preparation steps: S1. Add Fe3O4@SiO2 magnetic nanoparticles to anhydrous toluene with a mass of 4 to 5 times that of Fe3O4@SiO2 magnetic nanoparticles, ultrasonically disperse for 10 to 15 minutes, then add allyltrimethoxysilane with a mass of 3 to 4 times that of Fe3O4@SiO2 magnetic nanoparticles, stir and react for 24 to 26 hours at a temperature of 105 to 115°C and a speed of 300 r / min, transfer to a centrifuge tube after the reaction is completed, and centrifuge for 10 to 12 minutes at a temperature of 25 to 35°C and a speed of 8000 r / min to obtain modified Fe3O4@SiO2 magnetic nanoparticles; S2, adding sodium hydroxide, N, N'-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinylpyridine to deionized water 3 to 5 times the mass of methyl methacrylate, then adding modified Fe3O4@SiO2 magnetic nanoparticles 0.08 to 0.1 times the mass of methyl methacrylate, stirring evenly, stirring and reacting for 30 to 40 minutes at a temperature of 35 to 40 ° C, then adding N, N'-tetramethylethylenediamine 0.8 to 1.2 times the mass of methyl methacrylate, stirring evenly, reacting for 3 to 3.5 hours, standing for 1 to 2 hours after the reaction, and then washing the product with acetone and deionized water for 3 to 4 times respectively to prepare copolymer magnetic beads; S3. Add the copolymer magnetic beads to an ammonia solution with a mass fraction of 25-28% which is 10-15 times the mass of the copolymer magnetic beads to swell; at a temperature of 0-5°C and under nitrogen protection, add n-heptane with a mass fraction of 600-700 times the mass of the copolymer magnetic beads, stir for 30-40 minutes at a rotation speed of 450-500r / min, and then add 5-6 times the mass of the copolymer magnetic beads of tetraethyl orthosilicate solution at a uniform speed of 1mL / S. After the addition is completed, continue to stir the reaction for 3-4h. After the reaction is completed, filter, and use acetone and deionized water to wash the filtered product for 3-4 times respectively, and then dry it naturally to obtain modified copolymer magnetic beads.

2. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The Fe3O4@SiO2 magnetic nanoparticles include the following preparation steps: adding Fe3O4 magnetic nanoparticles to deionized water with a mass of 180 to 200 times that of the Fe3O4 magnetic nanoparticles, stirring for 10 to 20 minutes under nitrogen protection, heating to 75 to 85°C after uniform stirring, then dripping a Na2SiO3 solution with a mass of 20 to 22 times that of the Fe3O4 magnetic nanoparticles at a rate of 10 mL / h, adjusting the pH to 6 to 6.5 with a hydrochloric acid solution with a mass fraction of 36 to 38%, stirring for reaction for 3 to 3.5 hours after the dripping is completed, performing magnetic separation after the stirring is completed, and washing the separated product with anhydrous ethanol and deionized water for 3 to 5 times respectively, and then vacuum drying at a temperature of 55 to 65°C for 14 to 16 hours to obtain Fe3O4@SiO2 magnetic nanoparticles.

3. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The mass fraction of the Na2SiO3 solution is 12-14%.

4. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The Fe3O4 magnetic nanoparticles include the following preparation steps: adding FeCl3·6H2O to ethylene glycol with a mass of 30 to 35 times that of FeCl3·6H2O, stirring for 30 to 35 minutes, then adding anhydrous sodium acetate and polyethylene glycol, and continuing to stir for 30 to 35 minutes. After stirring, reacting at a temperature of 200 to 210°C for 48 to 50 hours, separating by magnetic force after the reaction is completed, and washing the separated products with anhydrous ethanol and deionized water for 3 to 5 times respectively, and then vacuum drying at a temperature of 55 to 65°C for 24 to 26 hours to obtain Fe3O4 magnetic nanoparticles.

5. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The mass of the anhydrous sodium acetate is 2.5 to 2.8 times that of FeCl3·6H2O.

6. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The polyethylene glycol is 0.7 to 0.75 times the mass of FeCl3·6H2O.

7. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The ethyl orthosilicate solution is prepared by mixing ethyl orthosilicate and n-heptane in a volume ratio of 1:

4.

8. The StarPure endotoxin-free ultrapure plasmid extraction kit according to claim 1, characterized in that: The mass ratio of the sodium hydroxide, N,N′-methylenebisacrylamide, ammonium persulfate, methyl methacrylate and vinyl pyridine is 0.28-0.3: 0.22-0.24: 0.8-0.9: 1: 0.8-0.

9.

9. The StarPure endotoxin-free ultrapure plasmid extraction kit extraction method is characterized in that: the StarPure endotoxin-free ultrapure plasmid extraction kit according to any one of claims 1 to 8 is used for extraction, comprising the following steps: Step (1), transferring the bacterial culture solution into a sterilized centrifuge tube, and collecting the bacterial precipitate by centrifugation; Step (2), adding the suspension to the bacterial precipitate of step (1), vortexing and oscillating to obtain a bacterial suspension; Step (3), adding a lysis solution to the bacterial suspension of step (2) to lyse the bacterial precipitate to obtain a bacterial lysis solution; Step (4), adding the binding solution to the bacterial lysate of step (3), centrifuging, taking the supernatant and transferring it to a centrifuge tube, then adding the modified copolymer magnetic bead suspension, standing at 25 to 35° C. for 3 to 5 minutes, and then placing the centrifuge tube in the magnetic field of a magnetic stand to remove the residual liquid; Step (5), adding washing solution to the centrifuge tube from which the residual liquid is removed in step (4), shaking and inverting 2 to 3 times, placing the tube in the magnetic field of the magnetic stand again, removing the residual liquid, repeating the process once, keeping the tube at rest for 5 to 10 minutes at 25 to 35° C., adding eluent, incubating at 25 to 35° C. for 3 to 5 minutes, placing the tube in the magnetic field again, extracting the remaining solution, and storing it at -20° C. The resulting solution is the high-purity plasmid obtained by extraction.